Efektivitas Penyaluran KUR (Kredit Usaha Rakyat) dan Pengaruhnya Terhadap Omzet Usaha Mikro di Kecamatan Gianyar (Studi Kasus pada Nasabah PT. Bank BPD Bali Cabang Gianyar) - BERATA, DEWA AYU MALINDA SARI; BUDIASA, I WAYAN; USTRIYANA, I NYOMAN GEDE (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
The Effectiveness of KUR (People’s business credit) and Influence Distribution on Micro Business Turnover in Gianyar District (Case Study on Customers of PT. Bank BPD Bali Branch Gianyar). UMKM are one of the important aspects in the economy, especially to move the wheels of the economy of the small and medium community. Various efforts have been made to promote UMKM, one of which is the provision of business capital in the form of People's Business Credit (KUR) by the banking sector. This study aims to determine the effectiveness of KUR distribution on micro business turnover. This research was conducted in Gianyar District with the research subjects of Bank BPD Bali customers, Gianyar Branch in 2016-2020. The population in this study were customers of KUR Bank BPD Bali Gianyar Branch in 2016-2020, totaling 105 customers, with sample total of 51 KUR customers. The data analysis technique used in this research is SEM-PLS analysis and effectiveness test with descriptive analysis. The results of this study indicate that the accuracy of the procedure has a positive effect on the turnover of micro businesses in Gianyar District. The accuracy of the use of funds has a positive effect on the turnover of micro businesses in Gianyar District. The accuracy of the amount of credit has a positive effect on the turnover of micro enterprises in Gianyar District. The accuracy of the credit load does not have a positive effect on the turnover of micro-enterprises in Gianyar District. The effectiveness of KUR distribution at PT. Bank BPD Bali Gianyar Branch for micro business owners in Gianyar District has been running effectively. Suggestions for further researchers is that it can be taken into consideration for further research by adding variables that are thought to increase the effectiveness of KUR distribution.